Peran Administrasi Perkantoran Dalam Meningkatkan Produktivitas Dan Koordinasi Antarbagian - Annisa, Nurin; Kurniadi, Ryan (Jurnal Syntax Fusion, 2024)
Office administration is a managerial function that plays a strategic role in supporting the smooth operation of organizations. This study aims to analyze the role of office administration in improving work productivity and facilitating interdepartmental coordination, as well as identifying factors that support the effectiveness of office administration in enhancing organizational performance. The research method employed is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. Data analysis was conducted descriptively with a focus on interpreting the meaning of the role of office administration in organizational life. The results show that neat and structured administration can simplify workflows, reduce task duplication, and accelerate decision-making processes, thereby directly impacting the productivity improvement of individuals and teams. Administration also functions as a formal communication medium that facilitates interdepartmental coordination through fast and accurate information distribution. Factors supporting the effectiveness of office administration include the quality of human resources, utilization of information technology, and good document management. The conclusion of this study is that office administration has a strategic role in creating work efficiency and building synergy between units so that organizational goals can be achieved optimally.